A Retrospective Clinicopathological Study of Malignant Ovarian Tumors: A 3 Year Experience in a Tertiary Health Care Center of Dhaka, Bangladesh (Journal of Dhaka Medical College, 2021)
Background: Ovarian tumors are a heterogeneous group of neoplasm that have become increasingly important now-a-days because of their large variety of neoplastic entities and gradually increased rate of mortality due to female genital cancers.Objectives: The aim of this study was to analyze the histopathological pattern and clinical presentation of malignant ovarian tumors according to the WHO classification of ovarian tumors [2003] in a tertiary care center of Dhaka, Bangladesh.Materials and Methods: This retrospective study included and studied a total of 54 cases of malignant ovarian tumors at the Department of Obstetrics and Gynecology, Popular Medical College Hospital, Dhaka, Bangladesh over a period of 3 years from Jan 2015 to Dec 2017.Results: The mean age was 47.44±14.24 years old (age ranged from 20-70 years). Of the 54 malignant ovarian tumors studied, the commonest histological pattern observed in the study was serous cyst adenocarcinoma constituting 26 cases (48.15%) followed by adenocarcinoma of ovary (25.9%), mucinous cyst adenocarcinoma (14.8%), endometriod adenocarcinoma (3.7%), dysgerminoma (3.7%) and ovarian choriocarcinoma (3.7%). High level of serum CA125 was found in most of the cases (n=48; 88.89%). The chief complaints were abdominal pain (n=38; 70.37%) and abdominal distension (n=29; 53.70%). Majority were admitted with less than one month duration of symptoms. The size of the tumor varied from 2.2 to 20 cm. All the patients were admitted in III and IV stage.Conclusions: Serous cyst adenocarcinoma was the common finding of this study. The prognosis and varying therapeutic strategies of malignant ovarian tumors necessitate an accurate histopathological evaluation.J Dhaka Medical College, Vol. 29, No.2, October, 2020, Page 100-105